FUNGSI PERADILAN TATA USAHA NEGARA DALAM MENYELESAIKAN SENGKETA LINGKUNGAN (STUDI GUGATAN ORGANISASI LINGKUNGAN HIDUP) - Fransisca Romana Harjiyatni; Sunarya Raharja (Fakultas Hukum Universitas Gadjah Mada, 2014)
This study aims to analyse: (1) The function of the Administrative Court in providing protection against environmental sustainability; (2) Constraints of the implementation of the administrative court functions in resolving environmental disputes. The results showed that: The function of the Administrative Court in providing protection toward the environment is not optimal yet. Administrative Court Decisions has not provided environmental sustainability because judges tend to be formalistic procedural in using their consideration. This is due to the presence of a number of constraints which include: government decision restrictions in the field of environment that can be disputed in the administrative court, there is no use of the principle of sustainable development as the consideration for the judge in deciding the case, and the judges’ less understanding about environmental problems. Penelitian ini bertujuan untuk menganalisis: (1) fungsi PTUN dalam memberikan perlindungan terhadap kelestarian lingkungan; (2) kendala-kendala pelaksanaan fungsi PTUN dalam menyelesaikan sengketa lingkungan. Hasil penelitian menunjukkan bahwa fungsi PTUN dalam memberikan perlindungan terhadap kelestarian lingkungan adalah belum optimal. Putusan-putusan Pengadilan TUN belum memberikan perlindungan kelestarian lingkungan hidup, karena hakim cenderung bersifat prosedural formalistik dalam menggunakan pertimbangannya. Hal ini disebabkan terdapatnya sejumlah kendala yang meliputi: adanya pembatasan KTUN di bidang lingkungan yang dapat menjadi obyek sengketa di PTUN, belum digunakannya asas pembangunan berkelanjutan sebagai pertimbangan hakim untuk memutus perkara, dan pemahaman hakim yang kurang mengenai persoalan lingkungan hidup.